DETERMINASI PENGUNGKAPAN EMISI KARBON PADA PERUSAHAAN DI INDONESIA - Rinaldi Tama Ramadhan; Husnah Nur Laela Ermaya; Ekawati Jati Wibawaningsih (Jurnal Akuntansi dan Pajak, 2021)
This study aims to examine the determination of the disclosure of carbon emissions in companies in Indonesia. The population in this study were companies listed on the Indonesia Stock Exchange for the period 2017 – 2019. The sampling technique was carried out using the purposive sampling method and resulted in 26 samples of companies. Hypothesis testing in this study is multiple linear regression. Based on multiple linear regression analysis and t-test shows that competition, type of industry, environmental performance and institutional ownership affect the disclosure of carbon emissions, while for profit growth, managerial ownership, company size and profitability do not affect the disclosure of carbon emissions. Keywords: Disclosure of Carbon Emissions, Profit Growth, Competition, Type of Industry, Environmental Performance, Managerial Ownership, Institutional Ownership, Company Size, Profitability